The Analysis of the Honesty and Responsibility Characters of Chemistry Education Study Program Students on Examinations - Suherman Suherman; Sitti Rahmawati; Kasmudin Mustapa; Detris Poba; Nur Azizah (Jurnal Akademika Kimia, 2021)
Honesty and responsibility should be a principle held by students. But, there are still problems of dishonesty and irresponsibility of students during exams. This study aimed to analyze the honesty and responsibility character of chemistry students during exams. The research samples were 39 students. Data were collected by observation and interviews technique, by using observation and questionnaires sheets. Data were analyzed by using descriptive statistics. The results showed that the honesty and responsibility of chemistry students were in the sufficient category where the percentage of honesty and responsibility of students based on the observation sheets was 43.6% and 49%, respectively. While the questionnaire responsibility students were 46.2% and 43.6%, respectively.